MENGELOLA PERUBAHAN: PERENCANAAN KONSERVASI GEDUNG DE JAVASCHE BANK SURABAYA - KWANDA Timoticin (Dimensi: Journal of Architecture and Built Environment, 2013)
The purpose of this paper is to present changes or interventions that allow to be applied in conservation of De Javasche Bank Surabaya in order to sustain the conservation main principle, authenticity. In this case, the problem of this study is how far a heritage building can be changed as a result of the interventions. Manage change in conservation planning of the building is important to be discussed for the interventions that carried out has to meet the conservation principles. Purposive sampling method is applied, therefore De Javasche Bank Surabaya is selected as the case study because at that time it was the only building that undergoing conservation planning in Surabaya. Conservation planning for the building that built in 1910 is guidance of interventions or changes prepared based on historical study, building documentation, and analysis of the the building transformation, the building structure, and material authenticity. Then, the results of the study was put into the acceptable interventions such as preservation of all the original and some existing elements; rehabilitation, restoration, reconstruction of the broken, ruined, missing elements and the hidden original element, including structure reinforcement; demolition of additional elements that cover the original elements; for the new elements such as MEP, minimum intervention principle can be met by using the existing openings; and to support the discernible principle in conservation, addition of new architecture elements with new materials as representation of the present era.